Carotenoid Levels in Maturing Grapes as Affected by Climatic Regions, Sunlight and Shade - Marais, J.; van Wyk, CJ.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
The effect of climatic region, degree of ripeness, sunlight and shade on carotenoid concentrations in Weisser Riesling and Chenin blanc grapes was investigated. Lutein and beta-carotene concentrations were higher in grapes from hot regions than grapes from cooler regions. In general, decreases in carotenoid concentrations were observed with an increase in ripeness. Also, grapes exposed to sunlight generally had lower carotenoid concentrations than shaded grapes. Both lutein and beta-carotene concentrations varied little between Weisser Riesling and Chenin blanc grapes at comparable ripening stages.